Mobile networks and cloud computing convergence for progressive services and applications - Rodrigues, Joel, 1972-, editor; Lin, Kai, 1979-, editor; Lloret Mauri, Jaime, editor (Hershey, P.A. : Information Science Reference, an imprint of IGI Global, 2014)
"This book is a fundamental source for the advancement of knowledge, application, and practice in the interdisciplinary areas of mobile network and cloud computing, addressing innovative concepts and critical issues"-- provided by publisher